The Association of Gut Microbiomes in Skin Cancer: Systematic Review and Meta–analysis - Ita Anggraini; Prima Kartika Esti; Eka Komarasari (Faculty of Medicine, Universitas Airlangga, 2026)
Background: The popularity of using probiotics to treat various diseases, including skin conditions, has been on the rise. It is widely recognized that skin cancer results from the uncontrolled growth of tumor cells, initiated by multiple contributing factors. Emerging research indicates that alterations in the gut microbiome may also play a role in the incidence of skin cancer. Purpose: This study was conducted to evaluate the relationship between gut microbiomes and skin cancer. Methods: This systematic review was conducted using the PubMed, ScienceDirect, and Cochrane Library databases for original articles published from 2015 to 2025. The focus of the study was the association of gut microbiomes in skin cancer. Then, the selected studies would be assessed for eligibility using the JBI critical appraisal, bias risk using RevMan tools, and meta-analysis using forest plotsesult: Of five studies, 261 subjects met the inclusion criteria. The combined odds ratio (OR) found in this study was 2.81, with a 95% confidence interval (CI) ranging from 1.97 to 3.99. According to the forest plot, there was a statistically significant overall effect observed (Z = 5.74; p < 0.00001), indicating a strong and meaningful association of the investigated variable. Although the studies related to the association of gut microbiomes in skin cancer were still limited, most of them showed similar results. Conclusion: There is an association of gut microbiomes in skin cancer. This study could lead to novel therapeutic strategies, where modulating the gut microbiome becomes a skin cancer treatment and prevention plan